Envisioning tax policy for accelerated development in India - M. Govinda Rao; Sudhanshu Kumar (Asia-Pacific Sustainable Development Journal, 2018)
The objective of the present paper is to demonstrate that despite several years of reform, the tax-GDP ratio in India is well below international standards and has been static over the last decade. Based on a crosscountry analysis of tax-GDP ratios in 115 countries over the period 2005-2015, an estimate is made of the extent of under-taxation in India. Considering that children in the age group of 0-14 years constitute about 40 per cent of the population of 1.3 billion in India, in the paper, it is argued that the tax-GDP ratio must be raised to enhance allocation to education, health care and physical infrastructure to ensure demographic dividends by providing the increasing workforce with productive employment opportunities. The reforms needed to raise the revenue productivity of the tax system while taking into account the best practice approach to tax reform are identified in the paper.